Building stronger networks for sustainable climate services in West Africa - Ouedraogo, Adama; Ouedraogo, Mathieu; Byandaga, Livingstone; Mvuyibwami, Patrick; Mbarushimana Kagabo, Desire; Laderach, Peter Roman Django (2025)
Bundled Climate Information Services (CIS) and Climate-Smart Agriculture (CSA) business models in West Africa are undermined by fragmented organizational networks, despite their potential to enhance agricultural resilience. A study analyzing organizations in Ghana, Mali, and Burkina Faso reveals three distinct but flawed national profiles. Ghana's network is strong and privately-sector led but critically lacks any financial institutions or NGOs. Mali has the largest and most sectorally balanced network, yet its organizations operate in silos with poor integration. Burkina Faso's network is moderately connected but is overly dominated by the public sector, making it vulnerable to government funding fluctuations. Beyond these country-specific issues, the study identified crippling region-wide weaknesses. A critical lack of funding mechanisms is evident, with financial partnerships constituting a mere 4.3% of all connections. Furthermore, cross-border collaboration is extremely limited, meaning countries do not learn from each other's experiences. All organizations are centralized in capital cities, creating a persistent "last-mile" problem where services fail to reach the rural farmers who need them most. While data sharing is common, poor policy coordination leads to duplicated efforts and inefficient resource use. The findings demonstrate that strategic, targeted interventions are needed to transform these fragile networks. Each country requires a unique pathway, such as recruiting financial institutions and NGOs in Ghana, improving integration in Mali, and diversifying away from public sector dominance in Burkina Faso. Regionally, priorities include establishing platforms to boost cross-border collaboration and creating strategies to engage the financial sector. This evidence shows that fixing the specific structural gaps in these organizational networks is essential for building sustainable climate service models that can effectively support West African farmers.